Peningkatan intensitas kejahatan transnasional terkait penyelundupan narkotika di Bali oleh WNA (2022) - Putu Vivien Alila Dewi; I Made Anom Wiranata; Sarah Abigail (Penelitian Ilmu Pengetahuan Sosial, 2024)
Solid sovereignty is considered to create a strong defense and security system for a country. However, with the emergence of globalization, countries are faced with new challenges, especially in fighting transnational crime. Indonesia as a strategic archipelagic country faces non-traditional security threats, especially on the island of Bali which is an international tourism destination. The aim of writing this journal is to find out the intensity of the quantity of foreign arrivals to Bali in 2022, then understand how cases of narcotics abuse can increase transnational crimes in Bali and what the process of handling cases of narcotics abuse in Bali is. By using a qualitative descriptive method to examine the increase in the intensity of transnational crimes related to narcotics smuggling in Bali by foreigners in 2022. Thus, a result was obtained, namely an increase in transnational crimes such as drug trafficking, showing the impact of globalization on national security. Therefore, it is important for countries to strengthen defense and security systems to maintain sovereignty amidst the challenges of rapidly growing globalization.